2019
DOI: 10.34087/cbusbed.525733
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Healthy Life Style Behaviors and Quality of Life of Nursing Students

Abstract: Bu araştırma, hemşirelik öğrencilerinin sağlıklı yaşam biçimi davranışları ile yaşam kaliteleri arasındaki ilişkinin belirlenmesi amacıyla planlandı. Gereç ve Yöntem:Kesitsel tipte yapılan bu araştırmanın evrenini, bir vakıf üniversitesinde eğitim alan 255 öğrenci, örneklemi ise araştırmaya katılmayı kabul eden 181 öğrenci oluşturdu. Araştırma verileri etik kurul ve kurum izni tamamlandıktan sonra; 31 Ocak-10 Şubat 2017 tarihleri arasında Kişisel Bilgi Formu, Sağlıklı Yaşam Biçimi Davranışları-II ve SF-36 Form… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
1
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 8 publications
1
1
1
Order By: Relevance
“…In another study, the health-promoting lifestyle behaviors of those with an eating disorder tendency were evaluated using HPLP-II, and it was observed that they adopted health-promoting lifestyle behaviors more, in contrast to our study's results [31]. In another study using BMI values and the HPLP-II scale, no difference was found between BMI and the HPLP-II's subscales [22].…”
Section: Discussioncontrasting
confidence: 97%
See 2 more Smart Citations
“…In another study, the health-promoting lifestyle behaviors of those with an eating disorder tendency were evaluated using HPLP-II, and it was observed that they adopted health-promoting lifestyle behaviors more, in contrast to our study's results [31]. In another study using BMI values and the HPLP-II scale, no difference was found between BMI and the HPLP-II's subscales [22].…”
Section: Discussioncontrasting
confidence: 97%
“…In the present study, it is thought that the low score in the subscale of exercise may be a result of the increase in the sedentary lifestyle of young people due to the recent development of technology and the increase in the widespread use of social media among young people. In addition, this result may be the result of midwifery students not knowing the importance of physical activity enough or not turning it into a health-promoting behavior [22]. The results in the HPLP's subscales' scores of midwifery students are similar to other studies conducted with the faculty of health sciences students.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation